The nightless city or the history of the Yoshiwara Yukwaku - Becker, J. E. De (Olympia Press, 1971)
Based on de Becker's experiences in Japan during the late 1890s. The story is told through the eyes of "The Lily," a girl with extraordinary beauty and superstar muscular control who finds herself sold into the life at an early age. Utilizing her special skill and a bit of luck, she makes her way to the top, Horatio-Alger style.